2017
DOI: 10.1002/adfm.201701950
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced Magnetocaloric Effect from Cr Substitution in Ising Lanthanide Gallium Garnets Ln3CrGa4O12 (Ln = Tb, Dy, Ho)

Abstract: A detailed study on the crystal structure and bulk magnetic properties of Cr substituted Ising type lanthanide gallium garnets Ln 3 CrGa 4 O 12 (Ln = Tb, Dy, Ho) is carried out using room temperature powder X-ray and neutron diffraction, magnetic susceptibility, isothermal magnetization, and heat capacity measurements. The magnetocaloric effect (MCE) where the geometry of the magnetic lattice prevents all the nearest-neighbor magnetic interactions from being satisfied simultaneously. [8] This suppresses or i… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
51
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 55 publications
(52 citation statements)
references
References 49 publications
0
51
1
Order By: Relevance
“…Solid state caloric refrigerants are one efficient alternative for such applications; 4 recent advances have been made in developing magnetocalorics with good performance at low temperatures under fields that can be generated using permanent magnets, required for energy efficient and practical magnetocaloric devices. [5][6][7][8][9] In recent years work on magnetocaloric materials has extended from purely ionic systems to those containing molecular building blocks and this appears a very promising route forward for developing improved materials. [10][11][12] The paramagnetic magnetocaloric effect (MCE) is an entropically driven cooling process that occurs when paramagnets are in a cycled magnetic field.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Solid state caloric refrigerants are one efficient alternative for such applications; 4 recent advances have been made in developing magnetocalorics with good performance at low temperatures under fields that can be generated using permanent magnets, required for energy efficient and practical magnetocaloric devices. [5][6][7][8][9] In recent years work on magnetocaloric materials has extended from purely ionic systems to those containing molecular building blocks and this appears a very promising route forward for developing improved materials. [10][11][12] The paramagnetic magnetocaloric effect (MCE) is an entropically driven cooling process that occurs when paramagnets are in a cycled magnetic field.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, however, literature has shown that materials containing cations with strong Ising anisotropy improves the magnetocaloric effect in powders under the low applied magnetic fields that can be generated using a permanent magnet (o2 T). 5,7,17 This surprising result is an outcome of the greater ease of magnetisation of these materials under low applied fields, but the microscopic cause of this remains unknown. Uncovering how magnetic interactions in such compounds are best optimised to improve magnetocaloric performance requires an understanding of these materials at the microscopic level, which is most readily achieved using neutron scattering rather than indirect bulk property measurements.…”
Section: Introductionmentioning
confidence: 99%
“…A and X are both restricted to non-magnetic cations as inclusion of magnetic cations on the A and X sites gives rise to additional magnetic phenomena [16][17][18][19][20][21]. The garnets crystallise in a cubic structure and contain three distinct cation sites based on the coordination with oxygen: dodecahedral occupied by Ln, octahedral occupied by A and tetrahedral occupied by X, Figure 1a.…”
Section: Introductionmentioning
confidence: 99%
“…The Cr 3+ substituted lanthanide gallium garnets, Ln3CrGa4O12 (Ln = Tb, Dy, Ho), also show an increase in TN by a smaller factor than on Mn 3+ substitution. 40 Neutron diffraction is required to elucidate the magnetic structure in these cases but this hints at a universal mechanism for relieving the magnetic frustration in Ising lanthanide garnets which is tuneable through control of the extent and type of magnetic ion substitution. e) The Ho 3+ quasi-spin couples ferromagnetically with the Mn 3+ spins located above and below the triangle.…”
Section: Main Textmentioning
confidence: 99%